Iowa RBA, April 28, 1997 - Fuller, James L.et al; Proescholdt, Market al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for April 28, 1997. Highlights of the update include sightings of a Long-tailed Duck and a Cinnamon Teal as well as the continued presence of a Red-throated Loon and a Pacific Loon. Also included are handwritten notes for the next week's update with sightings of a White-winged Dove, Western Grebes, and Greater Prairie-Chickens. Epson - sheet feed/flatbed